Star-forming S0 galaxies in the SDSS-IV MaNGA survey. Issue 1 (13th November 2021) - Xu, Ke; Gu, Qiusheng; Lu, Shiying; Ge, Xue; Xiao, Mengyuan; Contini, Emanuele
ABSTRACT: To investigate star-forming activities in early-type galaxies, we select a sample of 52 star-forming S0 galaxies (SFS0s) from the SDSS-IV MaNGA survey. We find that SFS0s have smaller stellar masses compared to normal S0s in MaNGA. After matching the stellar mass to select the control sample, we find that the mean Sérsic index of SFS0 bulges (1.76 ± 0.21) is significantly smaller than that of the control sample (2.57 ± 0.20), suggesting the existence of pseudo-bulges in SFS0s. After introducing the environmental information, SFS0s show smaller spin parameters in the field than in groups, while the control sample has no obvious difference in different environments, which may suggest different dynamical processes in SFS0s. Furthermore, with derived N/O and O/H abundance ratios, SFS0s in the field show nitrogen enrichment, providing evidence for the accretion of metal-poor gas in the field environment. To study the star-formation relation, we show that the slope of the spatially resolved star-formation main sequence is nearly 1.0 with MaNGA integral field unit data, confirming the self-regulation of star-formation activity on kpc scales.